UKRAINE IN THE WORLD INVESTMENT SPACE - Смаль, Валентина; Бульба, Юлія (Human Geography Journal, 2015)
Thе paper is devoted to the analysis of the participation of Ukraine in international investment processes, the level of its involvement into the global capital movements including comparison with other countries. The basic indicators that reveal the position of Ukraine in World exports and imports of capital are analyzed. The main trends of FDI inflow to Ukraine economy are examined. The competitive advantages and limiting factors foreign investment attracting are identified. The measures that have be taken to strengthen the engagement and effective use of foreign capital are proposed in the article.